FEATURES OF FORMING A MECHANISM FOR SUSTAINABLE INDUSTRIAL DEVELOPMENT BASED ON EFFICIENT USE OF RESOURCES - O. E. Astafyeva (Publishing House of the State University of Management, 2020)
The features of the formation of the mechanism of sustainable development of industry on the basis of new principles of effective use of resources, based on the coordination of the volume of involvement of resources in the production process, taking into account the possibilities of reproduction and knowledge economy have been presented. The resource potential of the industry as part of the socio-economic system of the industry has been considered, characterized not only by the limit of production growth, but also by the technological capabilities of the industry, which affects the potential growth of the economy as a whole. It has been proposed to determine the growth of industrial sectors of the economy through the formation of a mechanism of sustainable development, which allows you to determine the growth potential by changing the principles of involving resources in the production process, taking into account innovative capabilities of the industry and rational allocation. The possibility of allocation of resources has been defined on the basis of substitution determined by the emergence of new technologies and the dynamics of their implementation in the industry.